Massive Hematochezia: A Complication of Methamphetamine-Induced Vasculitis Treated by Transcatheter Hemostasis - Daniel P. Link; Yung-Wei Chi (Case Reports in Radiology)
A long-term, heavy methamphetamine user with life-threatening rectal hemorrhage was treated with transcatheter occlusion of the bleeding arteries. The bleeding blood vessels were vulnerable submucosal arteries, part of the collateral supply to the distal colon. Visceral arteriography demonstrates severe arterial stenotic lesions of the celiac axis, superior mesenteric artery and the inferior mesenteric artery. Collateral vessels were seen with corkscrew morphology similar to that seen with thromboangiitis obliterans.